(untitled) - Carrado, Charles J. (Boston, 2005)
The target market for this text is an introductory undergraduate course in which students have relatively little familiarity with investments and would like a practical and applied type of text. The approach of this undergraduate investments text reflects two central ideas: A consistent focus on the student as an individual investor or investment advisor, a consistent, unified treatment of the four basic types of financial instruments stocks, bonds, options, and futures focusing on their characteristics and features, their risks and returns, and the markets in which they trade.
Keywords: Investments